Recent Advances in Electrochemical Aptasensors for Detection of Biomarkers - Marjan Majdinasab; Jean Louis Marty (MDPI AG, 2022)
The early diagnosis of diseases is of great importance for the effective treatment of patients. Biomarkers are one of the most promising medical approaches in the diagnosis of diseases and their progress and facilitate reaching this goal. Among the many methods developed in the detection of biomarkers, aptamer-based biosensors (aptasensors) have shown great promise. Aptamers are promising diagnostic molecules with high sensitivity and selectivity, low-cost synthesis, easy modification, low toxicity, and high stability. Electrochemical aptasensors with high sensitivity and accuracy have attracted considerable attention in the field of biomarker detection. In this review, we will summarize recent advances in biomarker detection using electrochemical aptasensors. The principles of detection, sensitivity, selectivity, and other important factors in aptasensor performance are investigated. Finally, advantages and challenges of the developed aptasensors are discussed.